2002
DOI: 10.1088/0305-4470/35/12/303
|View full text |Cite
|
Sign up to set email alerts
|

On directed interacting animals and directed percolation

Abstract: Abstract.We study the phase diagram of fully directed lattice animals with nearest-neighbour interactions on the square lattice. This model comprises several interesting ensembles (directed site and bond trees, bond animals, strongly embeddable animals) as special cases and its collapse transition is equivalent to a directed bond percolation threshold. Precise estimates for the animal size exponents in the different phases and for the critical fugacities of these special ensembles are obtained from a phenomeno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 49 publications
(161 reference statements)
1
13
0
Order By: Relevance
“…We have found that the number n ( )  of required configurations grows roughly by a factor of 1.9 (for n20) when passing from n to n 1 ( ) + , and for the largest strip this number is 24 352 697 ( )  = . It is interesting to note that size of the transfer matrix T n (x) for directed animals on cylinders can be further significantly reduced [4], since its rank is smaller than dimension n ( )  . Let us note, however, that the size of the matrix elements of such a reduced matrix (polynomials in x) grows much more rapidly with n than in the case of T n (x); for simplicity, in this paper we used T n (x) matrices only.…”
Section: Directed Lattice Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that the number n ( )  of required configurations grows roughly by a factor of 1.9 (for n20) when passing from n to n 1 ( ) + , and for the largest strip this number is 24 352 697 ( )  = . It is interesting to note that size of the transfer matrix T n (x) for directed animals on cylinders can be further significantly reduced [4], since its rank is smaller than dimension n ( )  . Let us note, however, that the size of the matrix elements of such a reduced matrix (polynomials in x) grows much more rapidly with n than in the case of T n (x); for simplicity, in this paper we used T n (x) matrices only.…”
Section: Directed Lattice Animalsmentioning
confidence: 99%
“…Due to a lack of exact results, a considerable portion of research activity on directed percolation has been devoted to the development of various numerical approaches. For two-dimensional systems quite accurate results were obtained using the transfer-matrix technique [2][3][4], Monte Carlo simulations [5] and, in particular, using the methods of series expansions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The related problem of directed lattice animals (DA) has been studied extensively [17,18,19,20,21,22,14,15,23,24,25,26,27]. It is generally believed that the loop-free condition does not affect the critical behavior, so that both systems should have the same exponents.…”
Section: D+1mentioning
confidence: 99%
“…The model of interacting directed animals on infinite strips of a square lattice has been studied in detail by using the transfer-matrix method coupled with the phenomenological renormalization group (PRG) approach [23]. Using this approach quite precise estimates of various quantities of interest have been obtained.…”
Section: Introductionmentioning
confidence: 99%